Sunteți pe pagina 1din 1

Aim for Success Form 4: Chapter 2 Quadratic Equations

Paper 1

1.

2(3 + x )(2 – x ) = x + 5

2(6 – 3x + 2 x x 2 ) = x + 5 2(6 – x x 2 ) = x + 5 12 – 2 x – 2 x 2 = x + 5

2 x 2 + 3 x – 7 = 0

= –3 ±

x

x = –3 ±

4

3 2 – 4(2)(–7)

2(2)

65

x = 1.266 or –2.766 (correct to 3 decimal places)

2.

3.

4.

The given roots are –2 and

3

2

.

Sum of roots = –2 +

3

2

= – 1

2

3

2

= –3

Product of roots = –2

Hence, the quadratic equation is

x 2 +

1

2

x – 3 = 0

2 x 2 + x – 6 = 0

4 x 2 + ( p – 1) x

= –1

4

a = 4, b = p – 1, c = 1

If the quadratic equation has two equal roots,

x 2 + ( p – 1) x + 1 = 0

= 0

p – 1) 2 – 4(4)(1) = 0

= 0

p 2 – 2 p – 15

p + 3)( p – 5) = 0

= 0

b 2 – 4 ac

(

p 2 – 2 p + 1 – 16

(

p = –3 or 5

3 x 2 + 2 x + 4 p = 0

a = 3, b = 2, c = 4 p

If the quadratic equation has real and distinct roots, then b 2 – 4 ac > 0. b 2 – 4 ac > 0 2 2 – 4(3)(4 p ) > 0 4 – 48 p > 0 – 48 p > –4

p

p

<

<

–4

–48

1

12

1

5. 2 x 2 + 11 x – 6 = 0 The given roots are α and β .

α + β = –

αβ =

c

a

=

b

= –

a

–6

2

11

2 .

= –3

The new roots are

α

3

and

β

3

Sum of new roots

=

=

α β

3 +

α + β

3

3

11

=

= –

2

3

11

6

Product of new roots

=

=

=

α

3

αβ

9

–3

9

= –

1

3

β

3

Hence, the required quadratic equation is

x 2 +

6 x 2 + 11 x – 2 = 0

11

6

x

1

3

= 0